2019
DOI: 10.3892/ijmm.2019.4294
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopolysaccharide and antimicrobial LL-37 enhance ICAM-1 expression and NF-κB p65 phosphorylation in senescent endothelial cells

Abstract: Cellular senescence is associated with the induction of a proinflammatory phenotype. Notably, senescent endothelial cells are detected at the sites of atherosclerotic lesions, suggesting the involvement of senescent endothelial cells in atherogenesis. Moreover, bacterial infection has been speculated to contribute to the pathogenesis of atherosclerosis. The present study investigated the effects of Gram-negative bacterial lipopolysaccharide (LPS) and LL-37 (a human antimicrobial peptide of the cathelicidin fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…They showed that LPS hyperactivates the expression of SASP molecules (IL-6, IL-1β, CCL2, TNF-α, CCL5, CXCL1, and VCAM-1) and signaling molecules (p38 MAPK and p65 NF-κB) in senescent HUVECs that are generated by ionizing radiation [ 98 ] and long-term culture [ 26 ]. This confirms our speculation that LPS enhances the expression of SASP molecules, including adhesion molecules, cytokines, and chemokines, by enhancing the NF-κB pathway in senescent ECs [ 93 ]. In addition, the SASP-enhancing effect of LPS was suggested in other cell types.…”
Section: Lps Enhances Sasp-associated Proinflammatory Responses Of Se...supporting
confidence: 90%
See 1 more Smart Citation
“…They showed that LPS hyperactivates the expression of SASP molecules (IL-6, IL-1β, CCL2, TNF-α, CCL5, CXCL1, and VCAM-1) and signaling molecules (p38 MAPK and p65 NF-κB) in senescent HUVECs that are generated by ionizing radiation [ 98 ] and long-term culture [ 26 ]. This confirms our speculation that LPS enhances the expression of SASP molecules, including adhesion molecules, cytokines, and chemokines, by enhancing the NF-κB pathway in senescent ECs [ 93 ]. In addition, the SASP-enhancing effect of LPS was suggested in other cell types.…”
Section: Lps Enhances Sasp-associated Proinflammatory Responses Of Se...supporting
confidence: 90%
“…This premise is consistent with the coexistence of LPS and SASP + cells (e.g., high ICAM-1-expressing SA-β-Gal + cells) on the vascular surface of atherosclerotic plaque [ 92 ]. Here, we present our results, demonstrating that LPS indeed increases ICAM-1 expression and NF-κB activation in senescent ECs as an SASP-enhancing agent under culture conditions [ 93 ].…”
Section: Lps Enhances Sasp-associated Proinflammatory Responses Of Se...mentioning
confidence: 99%
“…Afterward, we analyzed the morphological changes of gills and skin upon F. columnare infection, which showed similar results to those of IHNV-infected fish. In mammals, previous studies have shown that LPS cannot induce ICAM-1 expression in the intestinal epithelial cells ( 8 ), but enhanced ICAM-1 expression in the abnormal cells, such as senescent endothelial cells and cancer cells ( 43 , 44 ). Importantly, ICAM-1 plays a vital role in airway inflammation and bacterial clearance ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the findings of Lou et al indicated that TRIM22 can regulate autophagy of THP-1 cells by up-regulating the NF-κB/Beclin-1 pathway, and eliminate intracellular Mycobacterium tuberculosis by promoting autophagy (Lou et al, 2018 ). Also, it has been shown that LL-37 can promote the expression of NF-κB (Suzuki et al, 2019 ) and the induction of transcription activity of NF-κB (Lim et al, 2015 ). In the HaCaT cells, we speculated that LL-37 may induce autophagy by TRIM22/NF-κB/Beclin-1 pathway, which remains to be proved in future experiments.…”
Section: Discussionmentioning
confidence: 99%